2016
DOI: 10.1016/j.jclepro.2015.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Household-level transition methodology towards sustainable material footprints

Abstract: , +358 50 448 0940) Highlights • A new methodology for studying sustainability transition at household level • The methodology covers assessment, vision development, experiments and upscaling • Measuring and reducing material footprints according to the MIPS concept • Households developed their own roadmaps towards sustainable resource use • Relevant experiments were tested and future services simulated Abstract This paper presents a new household-level methodology for transition towards sustainability. The me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 40 publications
0
29
0
2
Order By: Relevance
“…The collective power of the sustainable consumption of this great Chinese tea-drinking population should not be ignored. As mentioned in Laakso and Lettenmeier's [84] study on a household-level methodology for the transition towards sustainability, it is believed that the findings of this study can contribute to a more sustainable level of consumption by encouraging relatively few consumption behavior changes in everyday life.…”
Section: Conclusion Limitations and Future Workmentioning
confidence: 77%
“…The collective power of the sustainable consumption of this great Chinese tea-drinking population should not be ignored. As mentioned in Laakso and Lettenmeier's [84] study on a household-level methodology for the transition towards sustainability, it is believed that the findings of this study can contribute to a more sustainable level of consumption by encouraging relatively few consumption behavior changes in everyday life.…”
Section: Conclusion Limitations and Future Workmentioning
confidence: 77%
“…engaged in a number of leisure time activities, from sports to culture and volunteering in local organisations. The results from the experiment demonstrated that natural resource use could be reduced by making relatively few changes: the participating households achieved significant resource intensity reductions in mobility, food, household energy use, goods and leisure time activities, with falls of between 25 and 54 per cent (Laakso and Lettenmeier 2016). However, these reductions varied markedly between households, particularly in the case of the resource intensity of everyday mobility:…”
Section: Methodsmentioning
confidence: 99%
“…A total of 212 ideas were received, of which 14 were experimented with. 4 The natural resource use of households was estimated on the basis of consumption surveys and the resource intensity coefficients of each activity based on previous research (see Laakso and Lettenmeier 2016). engaged in a number of leisure time activities, from sports to culture and volunteering in local organisations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wernick [8], K. Wiesen [9], C. Liedtkea [10], L. Mancini [11], S. Laaksoa [12]. Методика MIPS-аналізу в цих працях має об'єктом дослідження економічні системи і оперує до економічних характе-ристик, що потребує зміни її змістовності та математичної інтерпретації вхі-дної інформації і кінцевих результатів для отримання оцінки екологічності та небезпечного впливу господарської діяльності на об'єкти природного се-редовища.…”
Section: літературний оглядunclassified